The Adrenal Gland: A Fascinating Object of Research and Clinical Care Showcased at the 15th German Adrenal Conference in Dresden - Kroiss, Matthias; Bechmann, Nicole (Hormone and Metabolic Research, 2024)
Dear colleagues,When younger fellows ask for guidance on how to choose a research project, many aspects require consideration: how to select a supervisor and mentor, should one change the institution, how does the project boost the later professional career, what are personal and professional aims. As many can probably relate it is passion for the research topic, both by the fellow and the mentor, that will go a long way and most often result in successful project completion.